Build your own PC on a budget : a DIY guide for hobbyists and gamers - ueller, John, 1958- (2016)
"Design and assemble an inexpensive yet fast and reliable PCConstruct the PC of your dreams using the practical information contained in this hands-on guide. Build Your Own PC on a Budget explains step-by-step how to put together a customized computer that is affordable stable and powerful. Discover how to choose the parts that fit your needs safely connect and test components add video and peripherals install an operating system connect to the Internet and go wireless. Security maintenance and software updates are fully covered in this DIY book. Look inside a PC and understand how each component works. Decide what you want from your PC and develop a design plan. Create a cost-effective parts list and select the best vendors. Wire up the motherboard processor and add-on boards. Connect storage devices display adapters and peripherals. Securely connect to LANs WiFi networks and the Internet. Install your operating system device drivers and applications. Maintain your PC update software and back up your data"--.